2017
DOI: 10.1088/1361-6641/aa5584
|View full text |Cite
|
Sign up to set email alerts
|

Role of deposition and annealing of the top gate dielectric in a-IGZO TFT-based dual-gate ion-sensitive field-effect transistors

Abstract: The deposition of the top gate dielectric in thin film transistor (TFT)-based dual-gate ionsensitive field-effect transistors (DG ISFETs) is critical, and expected not to affect the bottom gate TFT characteristics, while providing a higher pH sensitive surface and efficient capacitive coupling between the gates. Amorphous Ta 2 O 5 , in addition to having good sensing properties, possesses a high dielectric constant of ∼25 making it well suited as the top gate dielectric in a DG ISFET by providing higher capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Similarly, D3 and D4 were fabricated by deposition of 30 nm Ta 2 O 5 as the TG dielectric over T3 and T4 by RF sputtering at 100 W power and 10% oxygen in Ar. Finally, a reservoir of size 10 × 0.1 mm 2 was made on top of all DGISFETs by photolithography with epoxy (SU 8 2002), , as shown in Figure f.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, D3 and D4 were fabricated by deposition of 30 nm Ta 2 O 5 as the TG dielectric over T3 and T4 by RF sputtering at 100 W power and 10% oxygen in Ar. Finally, a reservoir of size 10 × 0.1 mm 2 was made on top of all DGISFETs by photolithography with epoxy (SU 8 2002), , as shown in Figure f.…”
Section: Methodsmentioning
confidence: 99%
“…The values of sensitivity obtained by simulations were then compared with the experimental and theoretical values. The equations used in this simulation are the same, as used in our previous work, , except that a stacked BG dielectric is used here instead of a single-layer BG dielectric.…”
Section: Simulations and Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By reducing the level of native defects through optimising the deposition process for the gate dielectric, much additional processing is eliminated. However, it has been shown that where non-optimised deposition is necessary, annealing can significantly improve the device performance 242,243 .…”
Section: Defects In the Gate Dielectricmentioning
confidence: 99%
“…Lately, the development of pH sensors with a high stability and sensitivity for various biochemical and biological applications has attracted much attention from researchers. Since Bergveld introduced ion-sensitive field-effect transistors (ISFET) in 1970, different types of sensors have been used to estimate pH as well as other biochemical solutions, such as extended-gate field-effect transistors (EGFETs) [ 4 ], ion-sensitive field-effect transistors (ISFETs) [ 5 ], light-addressable potentiometric sensors (LAPSs) [ 6 ], and electrolyte insulator semiconductors (EISs) [ 7 ]. Among various types of sensors, the EIS system is considered one of the most exciting systems for chemical and biological sensing.…”
Section: Introductionmentioning
confidence: 99%